Motif Dan Kepuasan Penggunaan Instagram(Studi Kesenjangan Antara Motif Dan Kepuasan Penggunaan Media Sosial Instagram Pada Mahasiswa Universitas Muhammadiyah Surakarta Angkatan 2013) - Puspitorini, Dyah Ayu; , Agus Triyono, S.Sos, M.Si; , Nieldya N. (2016)
Social media is a used to publish the cont ent like a profile, activity, or even as a medium that gives space for communication and interaction in social networking in the siber. Social media has become the bridge to build the network of communication between personal. Through the profil, activities that was shared by users, become for them to communicate, for example like give coment in the photo. The type of this study is quantitative research, with a comparative approach. The population in this study is student of UMS 2015 academic years, sample research is 98 students and through proporsional random sampling. The techniques of collecting data using que ssionare. The techniques of analysis data this study is discrepancy analysis, or c aption/status uploaded social media users. The result of this study is: (1) level and gap between motif and gratification students of UMS social media users Instagram be seen from the aspects of information included in mi ddle category with the value of 19% gaps. (2) level and gap between motif and gratification student of UMS social media users Instagram be seen from the aspect of the identity of personal included in meddle category with thw value of 16% gaps. (3) level and gap between motif and gratification student of UMS social media users Instagram be seen from the aspect of the intagrasi and social interaction included in high category with the value of 16% gaps. (4) level and gap between motif and gratification student of UMS social media users Instagram be seen from the aspect of the entertainment of personal included in low category with the value of 22% gaps.